Mitigasi Bencana Kebakaran Lahan Gambut Berdasarkan Metode Network Analysis Berbasis GIS (Studi Kasus: Pulau Bengkalis) - Rizki Sahputra; Sigit Sutikno; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Peatland and forest fires disasters have become an annual issue that hit the area of Bengkalis Island and has caused many losses. A good disaster mitigation management is required to overcome this disaster. This study aims to identify and to analyze the number of optimum post needs that can service all areas in Bengkalis Island with a quick response time. In Bengkalis Island, there are 2 existing fire stations. Based on the service area analysis result, both stations only can service 50,05% area of Bengkalis Island. This study simulated the impact of covered service area by utilization more fire station. The simulation was utilized with 1,2,3 and 4 additional stations. Percentage of covered area with 1,2,3 and 4 additional fire station are 62,19% ; 71,70% ; 70,51% and 69,51% respectively. Covered area with quickest response time is increased simultaneously with every additional of fire stations. Keywords: Peatland Fires, Disaster Mitigation Management, Network Analysis, Service Area, Fire Station